A hybrid gel of hypergravity prepared NiO and polyaniline as Li-ion battery anodes. Issue 107 (19th October 2015) - Zhang, Ziyang; Liang, Meiying; Liu, Xinhua; Zhao, Fei; Wang, Baofeng; Li, Wenjun; Wang, Qigang
Abstract : This paper reports a mild preparation of NiO/PANI gel as a Li-ion battery anode, which exhibits enhanced electrochemical performance and cycle stability. Abstract : The hybrid gel of nickel oxide (NiO) and polyaniline (PANI) was prepared and applied as Li-ion battery anodes. Hypergravity NiO nanoparticles was obtained by the combination of hydrothermal treatment with a high gravity field of 1000 g in the 1, 2-dichlorobenzene/water system at 120 °C for 0.5 h. The porous PANI gel around the surface of the NiO nanoparticles can help the electrons and ions transfer between the NiO anode and electrolyte. Electrochemical measurements show that the NiO/PANI gel electrode composites exhibit a high reversible capacity of 455 mA h g −1 after 100 cycles at a charge–discharge rate of 0.5 C. The hybrid gel electrode may provide a favorable approach to optimize the electrochemical performance of electrode materials with large volume expansion and low electronic conductivity.